Four-operator reflected forward-backward algorithm for solving monotone inclusions involving Lipschitzian operator - Cao, Yu; Wang, Yuanheng; Ur Rehman, Habib; Shehu, Yekini; Yao, Jen-Chih (Communications in nonlinear science & numerical simulation, 2026)
In this work, using a discretisation of continuous-time dynamical systems, we design a novel splitting algorithm without the lifting technique for finding the sum of three maximal monotone operators and a monotone operator with Lipschitz continuity. In theory, we analyze the weak and strong convergence of the proposed splitting algorithm and show the sublinear convergence rate. The practical efficacy of the proposed algorithm is validated through image restoration experiments, where it outperforms existing methods.